Kajian Bentuk dan Makna Ragam Hias Songket Lepus Berakam Palembang - Netty Juliana; Qothrun Nada Ma ruf Batu Bara (Besaung : Jurnal Seni Desain dan Budaya, 2026)
Songket Lepus berakam is a form of cultural heritage in the form of textile craftsmanship originating from Palembang City. This study aims to examine the forms of decorative patterns and the meanings of the ornamental motifs of Songket Lepus Palembang, which are influenced by the environmental conditions and socio-cultural context of the Palembang community. In addition, this research also analyzes the forms of decorative motifs of Songket Lepus berakam, including their colors and philosophical values embedded in the motifs of Songket Lepus Palembang, in order to deepen knowledge of songket weaving craftsmanship. The methodology used in this research is a qualitative method with a socio-cultural approach. Songket Lepus berakam consists of three main motif sections, namely: (1) the border motifs of the fabric; (2) the central body motifs of the fabric; and (3) the end section motifs of the fabric. The border motifs feature decorative elements such as umpak bintang simbar. The central body motifs include kembang bintang, tanjung, and mawar patterns. Meanwhile, the end section motifs consist of pucuk rebung combined with kembang kunyit designs. The colors applied in this songket are gold and maroon red. All decorative motifs are systematically arranged, forming various geometric patterns. This study is expected to contribute to the knowledge of Indonesian textile crafts, which are rich in distinctive regional motifs and colors. Furthermore, it is hoped that the younger generation will be able to preserve the cultural heritage of Palembang society in line with contemporary technological developments